2011
DOI: 10.1089/ast.2010.0519
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Receptor and Membrane Interactions in FRTL-5 Thyroid Cell Strain in Microgravity

Abstract: The aim of this work was to analyze the possible alteration of thyrotropin (TSH) receptors in microgravity, which could explain the absence of thyroid cell proliferation in the space environment. Several forms of the TSH receptor are localized on the plasma membrane associated with caveolae and lipid rafts. The TSH regulates the fluidity of the cell membrane and the presence of its receptors in microdomains that are rich in sphingomyelin and cholesterol. TSH also stimulates cyclic adenosine monophosphate (cAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In such circumstance, our in vitro system had allowed us to demonstrate the presence of the TSHR and the increase of CHO in the culture medium. In hypogravity the cAMP production after TSH stimulation was inhibited with respect to control samples [11]. Here instead we observed similar results in hypergravity and in control samples.…”
Section: Discussionsupporting
confidence: 84%
“…In such circumstance, our in vitro system had allowed us to demonstrate the presence of the TSHR and the increase of CHO in the culture medium. In hypogravity the cAMP production after TSH stimulation was inhibited with respect to control samples [11]. Here instead we observed similar results in hypergravity and in control samples.…”
Section: Discussionsupporting
confidence: 84%
“…During the TEXUS-44 mission (launched on 7 February 2008 from Kiruna, in Northern Sweden), FRTL-5 cells were treated with TSH (Thyroid-stimulating hormone) at the onset of microgravity and were fixed after 6 min and 19 s, just at the end of the microgravity period [18]. The study has clearly shown that FRTL-5 cells undergo relevant changes in real microgravity conditions: they aggregate, chromatin condensates, and TSH receptors are shed in the culture medium.…”
Section: How Gravity Influences Thyroid Functionmentioning
confidence: 99%
“…[19][20][21] Therefore, devices that generate simulated microgravity (s-mg) conditions are most often used for tissue engineering.…”
Section: Devices To Generate Simulated Microgravitymentioning
confidence: 99%